2022
DOI: 10.3390/ph15060742
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Consumption of Ergothioneine Reduces Oxidative Stress and Amyloid Plaques and Restores Glucose Metabolism in the 5XFAD Mouse Model of Alzheimer’s Disease

Abstract: Background: Ergothioneine (ERGO) is a unique antioxidant and a rare amino acid available in fungi and various bacteria but not in higher plants or animals. Substantial research data indicate that ERGO is a physiological antioxidant cytoprotectant. Different from other antioxidants that need to breach the blood–brain barrier to enter the brain parenchyma, a specialized transporter called OCTN1 has been identified for transporting ERGO to the brain. Purpose: To assess whether consumption of ERGO can prevent the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 62 publications
1
9
0
Order By: Relevance
“…Ergothioneine is a naturally occurring dietary antioxidant and its uptake and accumulation are purely dependent on OCTN1 distribution. Beneficial effects of ergothioneine uptake against Aβ accumulations have been reported in our previous studies (Whitmore et al, 2022;Wijesinghe et al, 2023). We also reported significantly depleted OCTN1 transporters in the whole eye of transgenic 5XFAD mice by comparing it with age-matched C57BL/6J WT controls (Wijesinghe et al, 2023).…”
Section: Discussionsupporting
confidence: 77%
“…Ergothioneine is a naturally occurring dietary antioxidant and its uptake and accumulation are purely dependent on OCTN1 distribution. Beneficial effects of ergothioneine uptake against Aβ accumulations have been reported in our previous studies (Whitmore et al, 2022;Wijesinghe et al, 2023). We also reported significantly depleted OCTN1 transporters in the whole eye of transgenic 5XFAD mice by comparing it with age-matched C57BL/6J WT controls (Wijesinghe et al, 2023).…”
Section: Discussionsupporting
confidence: 77%
“…Neuroprotective capabilities of Ergo have been demonstrated in a range of in vitro and in vivo studies, however underlying mechanism remains unclear. Recently, we reported that longitudinal consumption of Ergo reduced Aβ plaques in the brain cross-sections, oxidative stress, and rescued glucose metabolism in a 5XFAD mouse model ( Whitmore et al, 2022 ). In our previous work, an efficient and reproducible preparation of [ 11 C]-labeled Ergo PET radioligand to detect threshold levels of oxidative stress in a preclinical animal model of AD was also reported ( Behof et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, EGT levels in human plasma decrease with advanced age and low levels of EGT in human plasma are associated with a range of age-related disorders 18,22 . Conversely, EGT supplementation shows promising results in animal models mimicking a broad spectrum of human diseases including Alzheimer’s disease and depression and during aging in mice 22,26,50,51 .…”
Section: Discussionmentioning
confidence: 99%